The effects of national parks on local communities' wages and employment in Costa Rica - Villalobos Fiatt, Laura (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Mag.Sc.) - CATIE, Turrialba (Costa Rica), 2009